Fearless : [large type] a novel - Craven, M. W. (Mike W.), 1968- (Craven, M. W. (Mike W.), 1968- Ben Koenig series, 2025)
"What is a truly fearless man capable of? They're about to find out. . . . Ben Koenig used to head the US Marshal's elite Special Operations Group. His team hunted the bad guys -- the really bad guys -- and he could find anyone. Then one day Koenig himself disappeared. Koenig has been on the run for six years. Now suddenly his face is on every television screen in the country and his cover is blown. A woman has gone missing, and her father will do anything to find her. He wants Koenig to discover what happened, no matter the cost. The trail leads Koenig to a small town in the burning heat of the Chihuahuan Desert, where some people have a secret they'll do anything to protect. But Koenig has a secret of his own: a unique condition that makes him unable to feel fear. Now Koenig is coming for them. And they should be afraid."--